2018
DOI: 10.1186/s12943-018-0908-8
|View full text |Cite|
|
Sign up to set email alerts
|

Invasion-related circular RNA circFNDC3B inhibits bladder cancer progression through the miR-1178-3p/G3BP2/SRC/FAK axis

Abstract: BackgroundIncreasing evidence has revealed that circular RNAs (circRNAs) play crucial roles in cancer biology. However, the role and underlying regulatory mechanisms of circFNDC3B in bladder cancer (BC) remain unknown.MethodsA cell invasion model was established by repeated transwell assays, and invasion-related circRNAs in BC were identified through an invasion model. The expression of circFNDC3B was detected in 82 BC tissues and cell lines by quantitative real-time PCR. Functional assays were performed to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
125
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(133 citation statements)
references
References 33 publications
8
125
0
Order By: Relevance
“…circRNA is one kind of endogenous noncoding RNA, which can stably exist in mammals. circRNAs are recently found to be involve in the development of numerous diseases, especially cancers . It was showed that OSCC tissues have abundant circRNAs, and multiple circRNAs significantly differentially expressed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…circRNA is one kind of endogenous noncoding RNA, which can stably exist in mammals. circRNAs are recently found to be involve in the development of numerous diseases, especially cancers . It was showed that OSCC tissues have abundant circRNAs, and multiple circRNAs significantly differentially expressed.…”
Section: Discussionmentioning
confidence: 99%
“…circRNAs are recently found to be involve in the development of numerous diseases, especially cancers. 20,21 It was showed that OSCC tissues have abundant circRNAs, and multiple circRNAs significantly differentially expressed. It was reported that hsa_circ_0008309 and hsa_circ_001242 was significantly downregulated in OSCC tissues, correlated with pathological differentiation of OSCC, and may act as a potential novel biomarker for the diagnosis and treatment of OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…A study found that circFNDC3B is significantly downregulated in BCa tissues and is associated with pathological T staging, grading, lymphatic invasion, and overall patient survival . Mechanistically, circFNDC3B binds directly to miR‐1178‐3p, which targets oncogene G3BP stress granule assembly factor 2 (G3BP2) mRNA .…”
Section: Tumor‐suppressive Circrnas and Cancersmentioning
confidence: 99%
“…A study found that circFNDC3B is significantly downregulated in BCa tissues and is associated with pathological T staging, grading, lymphatic invasion, and overall patient survival . Mechanistically, circFNDC3B binds directly to miR‐1178‐3p, which targets oncogene G3BP stress granule assembly factor 2 (G3BP2) mRNA . Another BCa‐associated circRNA, circITCH was found to be reduced in BCa tissues and cell lines, and expression of P21 and phosphatase and tensin homolog (PTEN) was upregulated by sponging of miR‐17 and miR‐224 .…”
Section: Tumor‐suppressive Circrnas and Cancersmentioning
confidence: 99%
“…An average person may lose~20-40% of skeletal muscle mass as well as muscle strength from by the time they reach 80 years of age (Carmeli et al 2002;Doherty 2003) and decline in skeletal muscle strength is predictive of disability and mortality in humans (Giampaoli et al 1999;Rantanen et al 1999;Rantanen et al 2012). Circular RNAs originating from this gene have been reported previously, and suggested to possess tumour suppressor activity (Liu et al 2018).…”
Section: Discussionmentioning
confidence: 93%